Interface formation of two- and three-dimensionally bonded materials in the case of GeTe–Sb2Te3 superlattices. Issue 45 (2nd November 2015) - Momand, Jamo; Wang, Ruining; Boschker, Jos E.; Verheijen, Marcel A.; Calarco, Raffaella; Kooi, Bart J.
Abstract : The ground state crystal structure of GeTe–Sb2 Te3 superlattices is actually a van der Waals heterostructure of Sb2 Te3 and rhombohedral GeSbTe. Abstract : GeTe–Sb2 Te3 superlattices are nanostructured phase-change materials which are under intense investigation for non-volatile memory applications. They show superior properties compared to their bulk counterparts and significant efforts exist to explain the atomistic nature of their functionality. The present work sheds new light on the interface formation between GeTe and Sb2 Te3, contradicting previously proposed models in the literature. For this purpose [GeTe(1 nm)–Sb2 Te3 (3 nm)]15 superlattices were grown on passivated Si(111) at 230 °C using molecular beam epitaxy and they have been characterized particularly with cross-sectional HAADF scanning transmission electron microscopy. Contrary to the previously proposed models, it is found that the ground state of the film actually consists of van der Waals bonded layers ( i.e. a van der Waals heterostructure) of Sb2 Te3 and rhombohedral GeSbTe. Moreover, it is shown by annealing the film at 400 °C, which reconfigures the superlattice into bulk rhombohedral GeSbTe, that this van der Waals layer is thermodynamically favored. These results are explained in terms of the bonding dimensionality of GeTe and Sb2 Te3 and the strong tendency of these materials to intermix. The findings debate the previously proposed switching mechanisms of superlattice phase-change materials and give new insights in their possible memory application.